Perilaku Menyimpang Seksual Siswa di SMA Baiturrahmah Padang Tahun 2015 - Rina Julianti; Marita Ronitua Sinabariba (Jurnal Medika Cendikia, 2016)
Each one among six of the world population are teenagers, in the US from 20 million IMS 30% are teenagers. In the RS. Terrain Pringadi condyloma disease, 35.4% age group 20-24 years. Data municipal police of Padang in 2014 obtained 38 SMA is often problematic. Data case of sexual behavior was highest in high school Baiturrahmah Padang 2014. Data 41 students who commit sexual behaviors that carry adult magazines, watch porn in Hp and kissing with your partner and do nasty and there are students who do things that are not natural to the one teacher. The research objective is to: determine the factors pernyebab occurrence of deviant sexual behavior in high school students Baiturrahmah Padang in 2015, knowing the form of sexual deviant behavior in high school students Baiturahmah Padang year 2015. This study used a qualitative approach and descriptive. Data collection through documentation study and interviews. Data analysis technique with data reduction, data presentation and conclusion. The technique of taking informants in this study is that the researchers are looking for snow boll key informants. The result showed the factors that influence student behavior is deviant parental controls, peer influences, behavioral dating, vidio porn, dating deviant habits and lack of sexual knowledge. As for other forms of sexual deviant behavior of the student is kissing, cuddling, masturbation masturbation and intercourse. From the above findings it can be concluded that students' sexual deviant behavior can occur anywhere and at any time, many factors that influence sexual deviant behavior of students and many other forms of sexual deviant behavior of students happened. Suggestions schools must provide extracurricular and provide health promotion to students by sources that match those of reproductive health